Constitution (Fundamental Law) of the Union of Soviet Socialist Republics. (As amended by the Supreme Soviet of the U.S.S.R., on February 25, 1947, on the recommendations of the Drafting Commission) (Washington, 1947)
Foreign Languages Publishing House.